Elite Investments in Party Institutionalization in New Democracies: A Two-Dimensional Approach - Bolleyer, Nicole; Ruth, Saskia P. (2018)
Abstract: This article conceptualizes party institutionalization and theorizes the conditions under which party elites invest in institutionalized parties in new democracies. We specify routinization and value infusion as two central dimensions of party institutionalization and theorize conditions relevant for party institutionalization across three central spheres: the party system, the state, and society. Constructing measures for routinization and value infusion based on expert survey data, we test our framework through multivariate regression models across parties in 18 Latin American democracies. As theoretically expected, some conditions (access to executive office, a party's formative environment, and group ties) significantly relate to both dimensions, while others (party system polarization and fragmentation, permanent state subsidies, and legislative office) relate to one dimension only. This highlights the multidimensionality of party institutionalization as a phenomenon and the c